MicroRNA-143 Activation Regulates Smooth Muscle and Endothelial Cell Crosstalk in Pulmonary Arterial Hypertension. Issue 10 (23rd October 2015) - Deng, Lin; Blanco, Francisco J.; Stevens, Hannah; Lu, Ruifang; Caudrillier, Axelle; McBride, Martin; McClure, John D.; Grant, Jenny; Thomas, Matthew; Frid, Maria; Stenmark, Kurt; White, Kevin; et al.
Abstract : Rationale: : The pathogenesis of pulmonary arterial hypertension (PAH) remains unclear. The 4 microRNAs representing the miR-143 and miR-145 stem loops are genomically clustered. Objective: : To elucidate the transcriptional regulation of the miR-143/145 cluster and the role of miR-143 in PAH. Methods and Results: : We identified the promoter region that regulates miR-143/145 microRNA expression in pulmonary artery smooth muscle cells (PASMCs). We mapped PAH-related signaling pathways, including estrogen receptor, liver X factor/retinoic X receptor, transforming growth factor-β (Smads), and hypoxia (hypoxia response element), that regulated levels of all pri-miR stem loop transcription and resulting microRNA expression. We observed that miR-143-3p is selectively upregulated compared with miR-143-5p during PASMC migration. Modulation of miR-143 in PASMCs significantly altered cell migration and apoptosis. In addition, we found high abundance of miR-143-3p in PASMC-derived exosomes. Using assays with pulmonary arterial endothelial cells, we demonstrated a paracrine promigratory and proangiogenic effect of miR-143-3p–enriched exosomes from PASMC. Quantitative polymerase chain reaction and in situ hybridization showed elevated expression of miR-143 in calf models of PAH and in samples from PAH patients. Moreover, in contrast to our previous findings that had not supported a therapeutic role in vivo, we now demonstrate a protective role of miR-143 in experimental pulmonary hypertension in vivo in miR-143−/− and anti-miR-143-3p–treated mice exposed to chronic hypoxia in both preventative and reversal settings. Conclusions: : MiR-143-3p modulated both cellular and exosome-mediated responses in pulmonary vascular cells, whereas inhibition of miR-143-3p blocked experimental pulmonary hypertension. Taken together, these findings confirm an important role for the miR-143/145 cluster in PAH pathobiology. Abstract : Supplemental Digital Content is available in the text.